1990
DOI: 10.1136/ard.49.9.708
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic study of the response to streptococcal carbohydrate antigen of the cell wall in rheumatic fever.

Abstract: An immunogenetic study of the response to streptococcal carbohydrate antigen of the cell wail was carried out on members of 15 multiplex families each having more than one sib affected with rheumatic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Pharyngeal infection with group A ß-hemolytic streptococci may lead to acute poststreptococcal rheumatic fever, especially in individuals who have an inherited recessive gene closely linked to the HLA locus that is responsible for high responsiveness to the streptococcal polysaccharide antigen of the cell wall. 7 It is known that the avidity of streptococcal binding to pharyngeal cells is determined by the HLA haplotype and is greater in individuals with rheumatic fever. 8 As demonstrated in a murine model, the pathogenesis of rheumatic fever includes crossreactivity of antibodies with the immunodominant epitope of group A streptococcal carbohydrate and cardiac valves, skin, kidney, and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngeal infection with group A ß-hemolytic streptococci may lead to acute poststreptococcal rheumatic fever, especially in individuals who have an inherited recessive gene closely linked to the HLA locus that is responsible for high responsiveness to the streptococcal polysaccharide antigen of the cell wall. 7 It is known that the avidity of streptococcal binding to pharyngeal cells is determined by the HLA haplotype and is greater in individuals with rheumatic fever. 8 As demonstrated in a murine model, the pathogenesis of rheumatic fever includes crossreactivity of antibodies with the immunodominant epitope of group A streptococcal carbohydrate and cardiac valves, skin, kidney, and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators also reported that all subjects who demonstrated a low antigenic response had no rheumatic fever, and their phenotypes were distinct from those of their paired siblings having rheumatic fever. Hafez et al 21 suggested that a recessive gene, in addition to a component contribution from other heterogeneous genes closely interrelated with human leukocyte antigen, may be involved in ARF pathogenesis. Their results are consistent with the observations by McCormack et al and Fontán et al 18,20 Although repeated exposure to streptococcal antigens may be necessary in the staging of ARF, some individuals without the genetic predisposition may never develop ARF nor produce elevated anti-My-1, anti-enolases, or other cross-reactive antibodies.…”
Section: Discussionmentioning
confidence: 98%
“…Although a recessive gene closely linked to the human leukocyte antigen locus appears to be a primary factor in the development of ARF, it is assumed that a variety of genes may additionally contribute to the disease spectrum of ARF. 21,33 Similarly, a major histocompatibility complex class I chain-related gene, specifically designated as gene A, has been suggested to be a significant partaker in the occurrence of uveitis. 31,34 Hafez et al 21 documented a higher response to the streptococcal polysaccharide cell wall antigen in all of the rheumatic fever sub- jects included in their study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations